2020
DOI: 10.1002/rth2.12426
|View full text |Cite
|
Sign up to set email alerts
|

Type 2A von Willebrand disease and systemic sclerosis: Vonicog alfa reduced gastrointestinal bleeding

Abstract: Essentials • Angiodysplasias are a common source of refractory gastrointestinal bleeding. • We report a case of a patient with inherited von Willebrand disease and systemic sclerosis. • A hemostaseological evaluation is crucial in the setting of refractory bleeding. • Vonicog alfa was used as prophylactic therapy and led to a reduction of angiodysplasias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Thus, because of the presence of ultra‐large multimers in rVWF and the proposed relationship between absence of HMWMs and pathophysiology of GI bleeding, it has been hypothesized that bleeding associated with angiodysplasia may respond better to rVWF than replacement pdVWF, which contains lower–molecular‐weight multimers 34–36 . Case reports have shown successful bleed resolution in previously refractory mucosal BEs, including refractory GI bleeding, with rVWF 37–39 . While most BEs treated with rVWF in the current report successfully resolved after rVWF, the extremely small sample size precludes drawing conclusions about the effectiveness of rVWF in treating GI BEs; prospective/registry studies are needed to fully explore rVWF effectiveness in GI BE.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus, because of the presence of ultra‐large multimers in rVWF and the proposed relationship between absence of HMWMs and pathophysiology of GI bleeding, it has been hypothesized that bleeding associated with angiodysplasia may respond better to rVWF than replacement pdVWF, which contains lower–molecular‐weight multimers 34–36 . Case reports have shown successful bleed resolution in previously refractory mucosal BEs, including refractory GI bleeding, with rVWF 37–39 . While most BEs treated with rVWF in the current report successfully resolved after rVWF, the extremely small sample size precludes drawing conclusions about the effectiveness of rVWF in treating GI BEs; prospective/registry studies are needed to fully explore rVWF effectiveness in GI BE.…”
Section: Discussionmentioning
confidence: 64%
“…[34][35][36] Case reports have shown successful bleed resolution in previously refractory mucosal BEs, including refractory GI bleeding, with rVWF. [37][38][39] While most BEs treated with rVWF in the current report successfully resolved after rVWF, the extremely small sample size precludes drawing conclusions about the effectiveness of rVWF in treating GI BEs; prospective/registry studies are needed to fully explore rVWF effectiveness in GI BE.…”
Section: Discussionmentioning
confidence: 86%
“…Our search identified 10,019 unique studies. After screening by title and abstract, and full‐text review, 61 studies were included in the review of which 54 had patient‐level data comprising 146 patients 8,10,15–66 and nine reported data usable at the population or survey level 9,11,19,51,67–71 (Figure 1). There were no new studies for inclusion identified by review of reference lists.…”
Section: Resultsmentioning
confidence: 99%